2013
DOI: 10.1186/1477-7525-11-50
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with Type 1 Diabetes: parental perceptions of child health and family functioning and their relationship to adolescent metabolic control

Abstract: BackgroundAdolescents with Type 1 diabetes (T1D) show less effective metabolic control than other age groups, partly because of biological changes beyond their control and partly because in this period of developmental transition, psychosocial factors can militate against young people upholding their lifestyle and medical regimens. Parents have an important role to play in supporting adolescents to self-manage their disease, but resultant family tensions can be high. In this study, we aimed to assess family fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 27 publications
5
70
0
2
Order By: Relevance
“…Considerable research has demonstrated the role of family conflict and warmth-caring behaviors on glycemic control in youth with type 1 diabetes (Anderson et al, 2002; Berg et al, 2008; Cohen et al, 2004; Hilliard et al, 2011; Ingerski et al, 2010; Moore et al, 2013), suggesting that self-management mediates this relationship (Hilliard et al, 2011, 2013). Results of this study provide further evidence of the critical importance of family conflict on youth quality of life, with self-management mediating this relationship as well.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable research has demonstrated the role of family conflict and warmth-caring behaviors on glycemic control in youth with type 1 diabetes (Anderson et al, 2002; Berg et al, 2008; Cohen et al, 2004; Hilliard et al, 2011; Ingerski et al, 2010; Moore et al, 2013), suggesting that self-management mediates this relationship (Hilliard et al, 2011, 2013). Results of this study provide further evidence of the critical importance of family conflict on youth quality of life, with self-management mediating this relationship as well.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the pediatric age group, it is possible to valorize the use of a motivational process as a way of guiding professionals to recognize and lead the user to changes (2) , since even children/adolescents and their families are aware of the need to modify certain habits, however this is not always put into practice (5) . With the child, support for self-care can be provided in two main areas: family and school (6) . On the other hand, adolescents are also influenced by their peers and online health information, since electronic media are more accessible, they tend to broaden health care and education (7) .…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Moor et al (2013), high family conflicts and their effects on family dynamics, parents' stresses, and poor control of blood sugar have been reported in families who had teenagers with type I diabetes (16).…”
Section: Introductionmentioning
confidence: 99%